214 Reconstruction of AUS Cuff Erosion: Defect Size Predicts Prognosis. Issue 1 (1st April 2022) - Chertack, N; Nealon, S; Joice, G; Caldwell, K; Kavoussi, M; Dropkin, B; Ortiz, N; Baumgarten, A; Shakir, N; Sanders, S; Hudak, S; Morey, A
ABSTRACT: Introduction: In-situ urethroplasty (ISU) has been proposed in conjunction with device explant as an acute management strategy after artificial urinary sphincter (AUS) cuff erosion. Previous studies have not shown a clear relationship between extent of erosion and long-term prognosis. Objective: We hypothesize that more extensive erosions are associated with higher rates of lower urinary tract complications (LUTC) and increased need for urinary diversion (UD). Methods: We performed a retrospective study of patients who underwent ISU for AUS cuff erosion from June 2007 to December 2020 with a minimum of 90-day follow up. Patients were stratified into two groups based on the degree of urethral erosion determined endoscopically at the time of device explant - mild erosions (<33% circumferential defect) and major erosions (> 33%). Outcomes included LUTC, AUS reimplantation, and UD. LUTC was defined as urethral strictures, diverticulum, fistulas, and erosions of a secondary AUS. UD was defined as suprapubic tube placement with or without urethral ligation or ileal conduit creation. Kaplan-Meier curves were created to compare outcomes between groups. Results: A total of 40 patients underwent ISU for urethral cuff erosion and met the follow-up criteria. Median patient age was 76 years old with median erosion defect size of 46% (IQR: 20-50%); 15 men (37.5%) had mild erosions and 25 (62.5%) had major erosions. The overall LUTC rate was 53.5% with significantly fewer complications noted with mild erosions (28.6% vs 65.4%, p = 0.002) (Figure 1). Ultimately, 35.0% of patients required permanent UD with decreased rates in the case of mild erosions (13.3% vs 48.0%, p = 0.04) (Figure 2). On Kaplan-Meier analysis, mild erosion was associated with improved LUTC-free and UD-free survival but not associated with AUS reimplantation. Conclusions: Prognosis after AUS cuff erosion is associated with size of the urethral defect. Patients with extensive cuff erosion are at high risk for LUTCs and permanent UD. Disclosure: Any of the authors act as a consultant, employee or shareholder of an industry for: Boston Scientific and Coloplast